The Influence of Job Satisfaction and Organizational Commitment on Employee Performance - Nina Nurhasanah; Siti Sarah; Purwanto SK (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In improving employee satisfaction, the company has tried to improve employee satisfaction through various programs such as improving incentives, creating the most comfortable working conditions or environment. The purpose of the study was to determine the extent to which job satisfaction and organizational commitment influence employee performance and the relationship between these variables. The research method used is a quantitative method with a survey approach using a Likert scale-based questionnaire. The research sample consisted of 110 State-Owned Banks employees who were domiciled in Jakarta and had worked for at least one year, with a purposive sampling technique. Data analysis was carried out using Structural Equation Modeling with the Partial Least Square (SEM-PLS) approach. The results of the study showed that job satisfaction had a positive and significant effect on organizational commitment, and organizational commitment had a positive and significant effect on employee performance. However, job satisfaction did not have a significant effect on employee performance directly.